ANALYSIS OF REPORTING AND CALCULATION OF PPH 21 INCOME TAX REPORT ON PERMANENT EMPLOYEES PT. TASINDO JAYA UTAMA SURABAYA - Nuryadi; Permatasari, Intan (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
This study aims to describe whether the reporting and calculation of PT. Tasindo Jaya Utama is in compliance with the Income Tax Law No.36 of 2008. The data studied were the results of interviews from PT. Tasindo Jaya Utama is related to income tax. Data collection techniques used are: field research, documentation, observation, interviews. The method used is descriptive qualitative. The data source used in this study is primary data. The result of this research is a comparison of the tax calculations from PT. Tasindo Jaya Utama with the author's calculations referring to the Law no. 36 of 2008, there is no difference in the income tax article payable and for tax deposits and reporting of PT. Tasindo uses Annual SPT and SSP, deposits and reports are made before the tax due date. PT. Tasindo Jaya Utama has made a deposit reporting and calculation in accordance with Law no. 36 of 2008.